Changes in habitat suitability influence non‐breeding distribution of waterbirds in central Europe. (26th December 2017) - Musilová, Zuzana; Musil, Petr; Zouhar, Jan; Adam, Matyáš
Abstract : Waterbird species have different requirements with respect to their non‐breeding areas, aiming to survive and gain condition during the non‐breeding period. Selection of non‐breeding areas could change over time and space driven by climate change and species habitat requirements. To help explain the mechanism shaping non‐breeding area selection, we provide site‐specific analyses of distributional changes in wintering waterbirds in central Europe, located at the centre of their flyways. We use wintering waterbirds as a highly dynamic model group monitored over a long‐time scale of 50 years (1966–2015). We identified species habitat requirements and changes in habitat use at the level of 733 individual non‐breeding (specifically wintering) sites for 12 waterbird species using citizen‐science monitoring data. We calculated site‐specific mean numbers and estimated site‐specific trends in numbers. The site‐specific approach revealed a general effect of mean winter temperature of site (seven of 12 species), wetland type (all species) and land cover (all species) on site‐specific numbers. We found increasing site‐specific trends in numbers in the northern and/or eastern part of the study area (Mute Swan Cygnus olor, Eurasian Teal Anas crecca, Common Pochard Aythya ferina, Great Cormorant Phalacrocorax carbo and Eurasian Coot Fulica atra ). Common Merganser Mergus merganser, Great Cormorant, Grey Heron Ardea cinerea, Common Pochard, Eurasian Coot and Common Moorhen Galinulla chloropus increased their site‐specific numbers on standing industrial waters with traditionally low fish stock. The site‐specific dynamics of bird numbers helped us to identify general preference for sites reducing winter harshness (warmer areas, running waters and more wetlands in the site vicinity), as well as indicating climate‐driven changes in spatial use of wintering sites (northern/north‐eastern range changes and changes in preference for industrial waters). This fine‐scale (site‐specific) approach can reveal large‐scale range and distribution shifts driven by climate and environmental changes regardless of the availability of large‐scale datasets.